Resilience and Growth Through Sustained Adjustment : The Moroccan Experience - Eken, Sena.; Cartiglia, Filippo; Decressin, Jorg.; Enders, Klaus-Stefan. (Washington, D.C. : International Monetary Fund, 1995)
This paper reviews and analyzes how Morocco overcame the economic and financial crisis it confronted at the beginning of the 1980s. It highlights the challenges that still confront the Moroccan economy and the lessons that can be drawn from Morocco's adjustment experience.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet